UJI VALIDITAS DAN RELIABITAS KUESIONER PENGETAHUAN, SIKAP DAN TINDAKAN TERKAIT IMUNISASI BCG (BACILLUS CALMETTE GUERIN) - Wulanda, Ayu; Delilah , Susan (Stikes Bina Husada, 2022)
Background : Knowledge, attitude and practice of parents about general training to achieve the goal or status of child vaccination. family and provider system characteristics and their effect on a child's status are important in assessing potential risks in maintaining protection against disease. The purpose of this study was to develop and validate an instrument for measuring the level of knowledge, attitudes and actions related to BCG. Methods: Research design quantitatively with cross sectional method. The research was carried out in 2 stages, the first was developing the instrument and the second stage was conducting a content validity test with assessment and input from experts conducted by the Bangka District Health Office and reliability testing. The research sample is 108 people, with accidental sampling technique. Cronbach's alpha value was used to assess the reliability of the questionnaire. Results: After going through two content tests with experts, and in the Pearson Product Moment statistical test for the three aspects, the results obtained were 25 statement items which were declared to be completely valid, consisting of nine knowledge statement items, 6 attitude statement items and 10 statement items. action. These twenty-five items were declared valid in content so that they could be tested to the next stage, namely reliability testing. After all statements are valid, it is continued with reliability test using Cronbach-Alpha. To find out the reliability, the way is to compare the value of r results with r tables, as the value of r results is the value